The Effect of Using the Sparkol Video Scribe Application on Learning Outcomes of Natural Sciences Students of UPT SMPN 3 Pitu Riase - Sanariya, Sanariya; M, Usman; Takdir, Muhammad; Hermansyah, Sam; Kasau, M Nurzin R. (International Journal of Educational Narratives, 2023)
Background. The population in this study were all students of class VIII UPT SMP Negri 3 Pitu Riase and the sample in this study were students of class VIII UPT SMP Negri 3 Pitu Riase. Purpose. This study uses quantitative methods and experimental research types that aim to examine the effect of the use of sparkol videoscribe on science learning outcomes of class VIII UPT SMP Negri 3 Pitu Riase students. Method. There are 2 variables in this study, the first is the independent variable, namely the effect of using sparkol videoscribe (x) and the second is the dependent variable, namely the science learning outcomes of class VIII students (y). Results. The test result data that has been collected is then analyzed using the mean formula. Based on the results of data analysis, it is obtained that the value of X = 78.88> Y value = 70.11 so that it can be seen that there is an effect of using sparkol videoscribe on the science learning outcomes of class VIII students of UPT SMP Negri 3 Pitu Riase. Conclusion. This shows that the working hypothesis which states that there is an effect of using sparkol videoscribe on the science learning outcomes of class VIII UPT SMP Negeri 3 Pitu Riase students. accepted.